2023
DOI: 10.1186/s12967-023-04406-x
|View full text |Cite
|
Sign up to set email alerts
|

Stargardt disease-associated in-frame ABCA4 exon 17 skipping results in significant ABCA4 function

Abstract: Background ABCA4, the gene implicated in Stargardt disease (STGD1), contains 50 exons, of which 17 contain multiples of three nucleotides. The impact of in-frame exon skipping is yet to be determined. Antisense oligonucleotides (AONs) have been investigated in Usher syndrome-associated genes to induce skipping of in-frame exons carrying severe variants and mitigate their disease-linked effect. Upon the identification of a STGD1 proband carrying a novel exon 17 canonical splice site variant, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In particular, the deletion of exons 10 and 11 (CNV 2) affects the region encoding part of the extracellular domain 1 of ABCA4 and contains several glycosylation positions involved in the recognition of the transported substrate [ 30 , 31 ]. Previous studies have suggested that the deletion of these in-frame exons is likely to result in severe or deleterious alleles [ 32 ]. CNV 11 is also an in-frame deletion, but both breakpoints fall in the exonic regions such that a new “fusion exon” composed of the start of exon 42 and the end of exon 44 would be created, likely affecting the folding and protein function.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the deletion of exons 10 and 11 (CNV 2) affects the region encoding part of the extracellular domain 1 of ABCA4 and contains several glycosylation positions involved in the recognition of the transported substrate [ 30 , 31 ]. Previous studies have suggested that the deletion of these in-frame exons is likely to result in severe or deleterious alleles [ 32 ]. CNV 11 is also an in-frame deletion, but both breakpoints fall in the exonic regions such that a new “fusion exon” composed of the start of exon 42 and the end of exon 44 would be created, likely affecting the folding and protein function.…”
Section: Discussionmentioning
confidence: 99%